The Role of Incentive Spirometry On Exercise Capacity, Breathing Symptoms, Depression Rate, and Quality of Life in NSCLC Patients with Chemotherapy - Dian Apriliana; Suradi Suradi; Ana Rima Setijadi (Indonesian Society of Respirology (ISR), 2021)
Backgrounds: Pulmonary rehabilitation is a non-pharmacological therapy that improves breathing capacity in lung cancer patients. This study aimed to determine the effects of incentive spirometry (IS) on exercise capacity, breathing symptoms, depression rates, and quality of life in lung cancer patients with chemotherapy. Method: This quasi-experimental study was done through purposive sampling of 32 lung cancer patients who underwent chemotherapy for at least three cycles at Dr. Moewardi General Regional Hospital, Surakarta, from December 2019 to February 2020.Data on 6 minutes walking test (6-MWT) to evaluate exercise capacity, breathing symptoms (BORG scale), level of depression (HRSD questionnaire), and quality of life (SGRQ questionnaire) . Results: Experimental group showed higher value of 6-MWT (72.75±152.50 meters vs. 31.81 ± 27.67, P=0.010), a decrease in the BORG scale (-1.78±1.72 vs. -0.38±1.67, P=0.013), Hamilton's score improvement (-2.25±5.12 vs. -4.25±5.34, P=0.075), and improvement in the SGRQ value (-10.77±9.82 vs. -0.08±11.16, P=0.752) compared to those of control group.